PENGARUH KOMITMEN ORGANISASIONAL, KEPUASAN KERJA DAN BUDAYA ORGANISASIONAL TERHADAP OCB KARYAWAN PADA TAMAN WANA VILLA AND SPA DI MELAYA, JEMBRANA - Darmawan, Kadek Andi; Satrya, I Gusti Bagus Honor (E-Jurnal Manajemen, 2018)
The purpose of this study is to analyze the effect of organizational commitment, job satisfaction and organizational culture on OCB. Sample size of the existing population is 41 people, using the saturated sampling technique. Data analysis technique used is multiple linear regression analysis, F test and t test. Data collection was done through questionnaires and interviews . Based on the results of the analysis found that organizational commitment, job satisfaction and organizational culture have a positive and significant effect on OCB. This shows that the higher the organizational commitment, the better the job satisfaction, and the stronger the organizational culture, the higher the OCB of employees.